Antibiotic resistance and cold-adaptive enzymes of antarctic culturable bacteria from King George Island - Morozova, Olga V.; Andreeva, Irina S.; Zhirakovskiy, Vladimir Yu; Pechurkina, Natalya I.; Puchkova, Larisa I.; Saranina, Irina V.; Emelyanova, Elena K.; Kamynina, Tatyana P. (Polar Science, 2022)
Cryotolerance in microorganisms from polar regions provides their survival through alternating freezing and thawing cycles. Our research was aimed at biodiversity analysis of culturable bacteria from the King George Island near Antarctica including their antibiotic resistance and cold-adaptive enzymes. Average bacterial density was estimated as 3 × 106 cells/mL but the number of colony-forming units (CFU) was essentially lower - (3.2–9.2)x103 cells/mL. Totally, 83 stable strains were isolated and identified using phylogenetic analysis of 16S rRNA gene nucleotide sequences and phenotypic traits. Main groups were the Gram-negative Pseudomonas and Duganella species as well as Gram-positive Arthrobacter spp. Besides, eubacteria Psychrobacter, Flavobacterium, Clavibacter, Aquaspirillum, Polaromonas, Actinibacterium, Shewanella, Kocuria and families Comamonadacea, Actinobacteridae were found. Genetic diversity of the bacteria was elevated with plasmids of different lengths in 33 strains but no correlation between the plasmids content and antibiotic resistance was found. Among cold-adapted enzymes antioxidant catalases (91.5%), peroxidases (57.5%), alkaline phosphatases (42.2%) prevailed; unspecific exonucleases were revealed in 16.9% strains and restriction endonucleases of type II - in 8.4% strains only. Lypases were detected in 24 strains (28.9%) and could facilitate membrane fluidity at low temperatures. Despite the antibiotic resistance the Antarctic cultivable eubacteria are mainly not pathogenic and may serve as sources of plasmids and cold-adapted enzymes for biotechnology. journal article